2018
DOI: 10.1016/j.physa.2018.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Master equation for the degree distribution of a Duplication and Divergence network

Abstract: Network growth as described by the Duplication-Divergence model proposes a simple general idea for the evolution dynamics of natural networks. In particular it is an alternative to the well known Barabási-Albert model when applied to protein-protein interaction networks. In this work we derive a master equation for the node degree distribution of networks growing via Duplication and Divergence and we obtain an expression for the total number of links and for the degree distribution as a function of the number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Network topological properties are also worth studying. There are a lot of traditional methods of calculating degree distributions of networks, e.g., mean-field method and master equations, which are applied under some specific situations to derive degree distributions of evolving networks [16] [17]. However, in this case of evolving networks with growth and deletion of nodes, it is difficult to obtain an analytical solution due to the non-homogeneity.…”
Section: Related Workmentioning
confidence: 99%
“…Network topological properties are also worth studying. There are a lot of traditional methods of calculating degree distributions of networks, e.g., mean-field method and master equations, which are applied under some specific situations to derive degree distributions of evolving networks [16] [17]. However, in this case of evolving networks with growth and deletion of nodes, it is difficult to obtain an analytical solution due to the non-homogeneity.…”
Section: Related Workmentioning
confidence: 99%
“…Though a single metabolic and a single protein-protein interaction (PPI) network are analyzed in the paper, these data sets composed of single elements are not enough to extract strong general conclusions about these biological systems. In [20] a version of the duplication and divergence model is analytically studied and it is observed that although it is possible to find parameter regions where the degree distribution will have a denser right tail, this distribution has a peak for low degrees indicating that it can not be fitted to a monotonically decreasing power-law function if one considers its whole range.…”
Section: Introductionmentioning
confidence: 99%
“…Hockin-Mann reaction network model and classic Becker-Döring-type models do not incorporate discreteness and stochasticity of the CF process, when it happens in confined space [22,13]. However, the Chemical Master Equation (CME) approach is widely used to address discreteness and stochasticity [23,24,25]. Solving the CME provides an evolving landscape in state space while the discrete form of the CME (dCME) can account for finite size effects [26,27,28].…”
Section: Introductionmentioning
confidence: 99%